ANALISIS SISTEM PERENCANAAN SUMBER DAYA MANUSIA PADA DINAS KESEHATAN KABUPATEN DELI SERDANG - Danish Iryad Gunawan; Nur Ahmadi Bi Rahmani (Universitas Sains dan Teknologi Komputer, 2022)
Human resource planning is intended to ensure that the needs of the organization's employees will be met on a regular and timely basis. However, the reality on the ground shows that the existing human resources at the Deli Serdang District Health Office are still minimal, meaning that their contribution to the organization is influenced by the planning itself. Despite these constraints and limitations, the Deli Serdang District Health Office continues to carry out its duties and functions. Therefore the aim of this study was to analyze the human resource planning system at the Deli Serdang District Health Office using study indicators, namely procurement, development, and placement. The findings show that the new employee recruitment system is implemented quite successfully according to the selection criteria of the hiring process. Education and training are used to develop human capital, and once new employees are hired, they are assigned to various work units based on their educational background and specialized knowledge, though often not in the way managers anticipate.